GTP-Binding Protein 1-Like (GTPBP1l) Regulates Vascular Patterning during Zebrafish Development - Yi-Hao Lo; Yi-Shan Huang; Yu-Chiuan Chang; Pei-Yu Hung; Wen-Der Wang; Wangta Liu; Ritesh Urade; Zhi-Hong Wen; Chang-Yi Wu (Biomedicines, 2022)
Genetic regulation of vascular patterning is not fully understood. Here, we report a novel gene, gtpbp1l (GTP-binding protein 1-like), that regulates vascular development in zebrafish. Amino acid sequence comparison and a phylogenetic study showed that gtpbp1l is conserved in vertebrates. Gtpbp1l mRNA is expressed in the vasculature during embryogenesis. Knockdown of gtpbp1l by morpholino impairs the patterning of the intersegmental vessel (ISV) and caudal vein plexus (CVP), indicating the role of gtpbp1l in vasculature. Further apoptosis assays and transgenic fish tests suggested that vascular defects in gtpbp1l morphants are not due to cell death but are likely caused by the impairment of migration and proliferation. Moreover, the altered expression of vessel markers is consistent with the vascular defects in gtpbp1l morphants. Finally, we revealed that gtpbp1l is regulated by VEGF/notch and BMP signaling. Collectively, these findings showed that gtpbp1l plays a critical role in vascular patterning during zebrafish development.